THE MAGELLAN SEAMOUNTS - EARLY CRETACEOUS RECORD OF THE SOUTH-PACIFIC ISOTOPIC AND THERMAL ANOMALY - Smith, W; Staudigel, H; Watts, A; Pringle, M (1989)
We present geophysical, geochemical, and geochronological data from two Early Cretaceous seamounts in the western Pacific Ocean which formed at melt sources in what is now French Polynesia. One seamount has an 40Ar/39Ar mineral age of 119.6 (±0.6, 1 σ) Ma, is flexurally compensated with an elastic plate thickness Te of 10 (±2) km, and is isotopically similar to the island of Mangaia, or toward the HIMU mantle end-member. The second has an age of 100.1 (±0.5, 1 σ) Ma, is compensated with a Te of 15 (±3) km, and is isotopically similar to Samoa, toward the EM-II "Dupal' mantle end-member. Geologic evidence suggests that the summits of these seamounts formed in shallow water, indicating that the underlying Jurassic seafloor was unusually shallow during the Cretaceous. Te values from these Cretaceous seamounts and localities in French Polynesia depart systemtically from the simple square root of age law which otherwise applies throughout the ocean basins. A thermal rejuvenation of the lithosphere beneath these seamounts during or prior to their emplacement may explain their unusually low Te values and subsidence history. These two Early Cretaceous seamounts exhibit the isotope, Te, and depth anomalies which have been previously described at young volcanoes in French Polynesia, and we infer that a South Pacific Isotopic and Thermal Anomaly has existed for at least 120 m.y. -Authors